Asian states at the Arctic Council: perceptions in Western States. (3rd July 2019) - Babin, Julie; Lasserre, Frederic
ABSTRACT: The upheavals caused by climate change in the Arctic region have contributed to its return to the geopolitical scene, leading to dramatic scenarios, such as the possibility of a new 'perceived Cold War', to the appropriation of Arctic resources, or the creation of 'Arctic sea highways' as objects of intense rivalries. If the Arctic States, including Russia, have actually operated in recent years a partial reorientation of their military and economic programs to the Arctic, it is nevertheless the growing interest of Asian States in this region that further drew the attention of western media and researchers in recent years. Indeed, many western media reflect concerns about the interest of Asian States for the Arctic and for the Arctic Council, and the possible loss of influence of the Arctic indigenous communities and States in the Arctic Council. Interrogations about the intentions of these new observers, India, Japan, South Korea and China (in particular), have fed concerns about their possible domination of the agenda of the Council. What is the attitude of these observers at the Arctic Council and are these concerns warranted?